Reasonable Accommodations for Persons with Disabilities in Public Services Under Law No. 8 of 2016 - Istiarsyah Istiarsyah; Dela Devita; Robiansyah Setiawan; Retno Triswandari; Lani Setyadi; Roslaini Roslaini (Westscience Press, 2026)
The fulfillment of public service rights for persons with disabilities remains an important issue in achieving substantive equality and preventing discrimination within state administration. Although Law No. 8 of 2016 concerning Persons with Disabilities has recognized the obligation to provide reasonable accommodations, the implementation of these obligations in public services continues to face various normative and institutional challenges. This study aims to analyze the legal framework governing reasonable accommodations for persons with disabilities in public services and examine its role in ensuring equal access based on human rights principles. This research employs a normative legal research method using a statutory approach and conceptual approach by examining relevant legal instruments, including Law No. 8 of 2016, Law No. 19 of 2011 concerning the Ratification of the Convention on the Rights of Persons with Disabilities, and regulations related to public services and accessibility. The results indicate that reasonable accommodation constitutes a fundamental legal obligation that requires public service providers to make necessary and appropriate adjustments to eliminate barriers experienced by persons with disabilities. Such accommodations include physical accessibility, procedural modifications, communication support, and inclusive service mechanisms. However, the implementation of reasonable accommodation remains limited due to the lack of detailed technical regulations, institutional capacity constraints, insufficient awareness among service providers, and weak accountability mechanisms. This study concludes that strengthening the implementation of reasonable accommodation requires regulatory harmonization, institutional commitment, capacity development, and effective monitoring systems. Reasonable accommodation should not be viewed as a form of special treatment but as a legal instrument to achieve substantive equality and ensure that persons with disabilities can fully exercise their rights in public services.